STRATEGI PEMERINTAH DALAM MENEKAN WANPRESTASI DALAM PENGADAAN KAPAL - Henry Aspan (Public Service and Governance Journal, 2023)
The sale and purchase of ships carried out by institutions with Indonesian citizenship and foreign countries must pay attention to various basic principles regulated by the government. These basic principles are used and must be established for the preparation of a contract so that the parties avoid things that can harm both the seller and the buyer in terms of administration in government. The administration of buying and selling ships is included in the class of buying and selling goods whose legality of ownership must be in accordance with the standards set by the government. When buying and selling or procurement contracts are regulated based on international private law which contains several theories related to the preparation of an agreement or contract. If a ship purchase agreement does not fulfill one of the administrative elements set by the government, the agreement is considered invalid or canceled. The validity of an agreement that has been made by the parties according to Gunawan Wijaja, namely the agreement must contain validity, both the validity of which is questioned by one of the parties or other matters. In implementing the sale and purchase agreement of ships between Indonesia and foreign countries, it must be by the provisions of the sale and purchase agreement that has been determined, which can refer to agreements in international private law. It is hoped that the government of both Indonesia and foreign countries can make a wise decision in determining the cancellation of an agreement by examining or exploring further the causes of the cancellation of the sale and purchase agreement.